C-section Delivery Is a Barrier to and Demographic-maternal-child Factors Have Mixed Effects on the Length of Exclusive Breastfeeding Under Nutrition Transition in Lebanon (P11-058-19). (13th June 2019) - Chehab, Rana; Nasreddine, Lara; Zgheib, Racha; Forman, Michele
Abstract: Objectives: The study aims to: estimate the prevalence of exclusive breastfeeding in Lebanon; and examine socio-demographic, maternal, and child-related determinants associated with exclusive breastfeeding for 40 days and 6 months. Methods: In a cross-sectional study of a nationally representative sample of 1005 Lebanese mother-child dyads, mothers of children < 5 years completed face-to-face interviews about child feeding practices, socio-demographic, maternal, and child characteristics. Exclusive breastfeeding versus mixed feeding or exclusive bottle feeding at 40 days or versus mixed feeding or bottle and solid feeding at 6 months served as the dependent variables. Multivariable logistic regression models were fitted and adjusted for significant covariates with P  < 0.10 in the unadjusted analysis. For all other analyses, P  < 0.05 indicated statistical significance. Results: 41% and 12% of the children were exclusively breastfed for 40 days and 6 months, respectively. Compared to the mixed fed or exclusively bottle fed at 40 days, the older the child at the interview the higher the odds by 1.4% per month of exclusive breastfeeding, whereas children delivered via C-section had a 26% or 53% lower odds of exclusively breastfeeding respectively. Also, compared to the exclusively bottle fed at 40 days, children in families with 3 + siblings had a 73% higher odds of exclusively breastfeeding, while children in families owning 2 + cars had a 58% lower odds of exclusively breastfeeding. Compared to the mixed fed at 6 months, children of overweight or obese mothers at the interview had 45% or 53% lower odds of exclusively breastfeeding respectively, whereas heavier children at the interview had a 10% per kg higher odds of exclusively breastfeeding. Compared to the bottle and solid fed at 6 months, children delivered via C-section and those in families owning 2 + cars had a lower odds of exclusively breastfeeding by 62% and 58% respectively. Conclusions: Socio-demographic, maternal and child characteristics influenced infant feeding practices over time in Lebanon. C-section delivery was consistently associated with a lower odds of exclusive breastfeeding for 40 days and 6 months. Reducing elective C-section delivery would enhance exclusive breastfeeding in a population undergoing social and nutrition transition. Funding Sources: Lebanese National Council for Scientific Research through its support to the Associated Research Unit (ARU) for "Nutrition and Non-communicable Diseases in Lebanon".